The structural characterization and UV-protective properties of an exopolysaccharide from a Paenibacillus isolate - Xu, Xiaodong; Ding, Zhao; Pu, Chunlin; Kong, Changchang; Chen, Shijunyin; Lu, Weiling; Zhang, Jianfa (Frontiers in Pharmacology, 2024)
Natural polysaccharides have attracted considerable interests due to diverse biological activities. In this study, an exopolysaccharide (EPS) producing strain was isolated from a forest soil sample, and was identified as Paenibacillus sp. 1538. The average molecular weight of the EPS was 5.48×10 6 Da, composed of glucose, mannose and galactose residues at a ratio of 2:2:1. The structure of the EPS was charactered by NMR and methylation analysis, indicating the repeating units of the EPS were →3)-β-D-Glcp (1→3) [β-D-Galp (1→2)-α-D-Glcp (1→2)]-α-D-Manp (1→3)-α-D-Manp (1→. In cultural HaCaT cells, the EPS reduced cytotoxicity and excessive ROS production induced by UVB irradiation. The EPS also exhibits an inhibitory effect on oxidative stress, inflammation, and collagen degradation found in the photodamage in mice. 1 H NMR-based metabolomics analysis for skin confirmed the protective effects of the EPS in UVB-induced skin injury. In conclusion, the EPS has the potential to be developed as a natural component in sunscreen.